Manipulated sex ratios alter group structure and cooperation in the brown-headed nuthatch. (12th March 2019) - Cox, James A; Cusick, Jessica A; DuVal, Emily H
Abstract: A biased adult sex ratio (ASR) can influence cooperative breeding behavior if the bias limits mating opportunities for the more abundant sex. We tested predictions associated with the ASR-cooperation hypothesis in the brown-headed nuthatch ( Sitta pusilla ). We manipulated ASR by cross-fostering known-sex nestlings within 2 large (≥100 ha) experimental plots for 5 years using a crossover design where each plot received an opposing male- or female-biased treatment for 2 consecutive years. A year with no manipulations followed before the bias was reversed on each plot for 2 additional years. Variation in ASR (adult males/total adults) was pronounced compared to background proportions (0.55) and ranged from a female bias in female-biased plots (0.47) to a strong male bias in male-biased plots (0.71). Sex ratios during the postbreeding period ranged more broadly (0.33 in female-biased plots vs. 0.74 in male-biased plots). Territory densities did not change significantly and allowed 6 predictions to be assessed. Consistent with predictions, the prevalence of cooperative breeding groups doubled under male-biased treatments and large cooperative groups appeared (≥2 male helpers vs. the single male helper most common prior to the experiment). These changes occurred despite increased dispersal of cross-fostered males in male-biased plots. Most juvenile females dispersed, but, consistent with predictions, the prevalence of female helpers increased under female-biased treatments. Manipulations did not alter the sex of nestlings produced nor extend the time that males served as helpers. Taken collectively, results support the ASR-cooperation hypothesis and the role that mate limitations play in cooperative breeding behavior. Abstract : Life is short. Why should any animal gamble away a chance to breed and help other individuals breed instead? Mate shortages could be 1 reason such behavior occurs. We tested this proposition by manipulating male and female availability in a small songbird. Female shortages yielded unusually large groups with nonbreeding male helpers. Male shortages led to more females willing to do the same. The study provided new insights on the long-studied phenomena of cooperative breeding.